1984
DOI: 10.1152/ajpgi.1984.247.1.g62
|View full text |Cite
|
Sign up to set email alerts
|

Binding of somatostatin to pancreatic acinar cells

Abstract: The binding of 125I-[Tyr11]somatostatin to guinea pig pancreatic acini was saturable and temperature, protein, and radioligand concentration dependent. Dissociation rate was very slow (t1/2 = 193 +/- 24 min). Scatchard analysis revealed a single class of binding sites with a Kd of 0.28 +/- 0.02 nM and a maximal binding capacity of 72 +/- 10.6 fmol/mg prot. There was a strong correlation between binding capacity and extracellular calcium concentration. Incubating acini in EGTA-containing medium with no added Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…The parameters of the SS receptors in the control rats were similar to those previously reported by others [12,42,47,48]. Although five SS receptor subtypes have been cloned [22], the exocrine pancreas appears to express only receptor subtype 2 (SSTR2) [5].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The parameters of the SS receptors in the control rats were similar to those previously reported by others [12,42,47,48]. Although five SS receptor subtypes have been cloned [22], the exocrine pancreas appears to express only receptor subtype 2 (SSTR2) [5].…”
Section: Discussionsupporting
confidence: 87%
“…SS was a partial antagonist of FKstimulated AC activity in pancreatic acinar membranes, in agreement with Heisler [17]. In this respect, it is well established that the inhibition of FK-stimulated AC activity by SS in pancreatic acinar cell membranes and other cell types involves three protein components found in the plasma membrane [12,42,43,47], ie, the SS receptor, the AC catalytic unit, and the GTP binding protein G i , which couples the SS receptor to the catalytic unit. Therefore, impairment of any of these three components by bombesin could attenuate the effect of SS.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…SS receptors have also been shown on acinar cells [3][4][5]. To our knowledge, glucagon receptors have not been reported to occur on acinar cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other islet hormones, i.e., somatostatin (SS), glucagon, and pancreatic polypeptide, are reported to suppress exocrine pancreatic function, at least in vivo [2]. Among these three peptides only SS has been proven conclusively to have specific receptors on acinar cells [3][4][5]. Histological studies have demonstrated that efferent vessels from islets go through neighbouring exocrine tissue as a fenestrated vessel or connect with surrounding acinar capillary beds (islet-acinar portal system) [6][7][8].…”
mentioning
confidence: 99%